On the incidence of chemically peculiar stars in the Large Magellanic Cloud - Paunzen, E. (2005)
With the aim to corroborate the result of a search for chemically peculiar stars in the Large Magellanic Cloud (LMC), we present measurements obtained from CCD imaging of two fields, one containing a young open cluster (NGC 1711). While for the latter field, including its surrounding we obtain a contribution of 3 per cent of chemically peculiar stars detectable by Δa photometry (i.e. the magnetic objects of this group), the second field yields about half of this value in good accordance with Maitzen et al.'s finding for NGC 1866, the surrounding field of which has been found to exhibit a very low value of such stars (0.3 per cent). Thus, we are faced with the fact that our incipient impression about a substantially lower appearance of magnetic chemically peculiar stars in the LMC as compared to the Galaxy continues to be valid. Most of the photometrically identified peculiar stars (from their historical origin denominated Ap stars) are located in the domain of the B-type stars. However, this is a selection effect due to the limiting magnitude of our observing conditions impeding the observation of fainter main-sequence stars. In addition to objects showing up as positive deviators in Δa photometry, we also discuss nine stars which appear opposite the main line of normal stars, and hence are negative deviators. For most of them, the interpretation as emission stars of B-type seems to be appropriate. The statistically relevant number of observations obtained so far in the LMC supports the view that the formation of magnetic peculiar stars has occurred there at a significantly lower rate.